THE ROLE OF INTERNATIONAL ASSESSMENT PROGRAMS PIRLS AND TIMSS IN TEACHING TECHNOLOGY IN PRIMARY EDUCATION (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the role of international assessment programs, PIRLS and TIMSS, in enhancing the functional literacy of students in primary school technology classes. The methodology of working with text, developing logical thinking, and strengthening interdisciplinary connections (STEAM) in teaching technology is highlighted. The article provides recommendations for designing practical tasks based on international criteria.